The study of miR-130a expression and its mechanism of action in peripheral blood endothelial progenitor cells (EPCs) in type 2 diabetes mellitus (T2DM) - Yawei Cai; Yao Zhu; Ning Xu; Tongen Chen (Scientific Reports)
Abstract TGF-β1 has been reported to suppress miR-130a expression, while being elevated in patients with type 2 diabetes mellitus (T2DM). And IL-18, a potential target of miR-130a, is also up-regulated in T2DM patients. In this study, we aim to investigate the potential involvement of the TGFβ1/miR-130a/IL-18 axis underlying the dysfunction of endothelial progenitor cells (EPCs) in T2DM patients. We performed luciferase assays to confirm the molecular binding between miR-130a, TGF-β1 and IL-18, and real-time PCR and ELISA were performed to observe the changes of TGF-β1, miR-130a, IL-18 and IFN-γ in different cell groups. Tube formation assay, cell adhesion assay and Transwell assay were performed to evaluate effect of TGF-β1/miR-130a/IL-18 axis on the EPCs functions. Accordingly, in EPCs treated with TGF-β1, we found that the levels of miR-130a were reduced, and its expressions were also negatively correlated with the expressions of IL-18 in the EPC groups. Luciferase assays validated IL-18 as a target gene of miR-130a. The over-expression of IL-18, as well as the knockdown of miR-130a, not only increased the expressions of TGF-β1 in EPCs, but also promoted the tube formation, adhesion and migration of EPCs. By contrast, the knockdown of IL-18, as well as the over-regulation of miR-130a, exhibited suppressive effect on the levels of TGF-β1, while inhibiting the tube formation, adhesion and migration of EPCs. In this study, we elucidated the impact of the TGFβ1/miR-130a/IL-18 signaling pathway on the function of EPCs, thus providing theoretical basis for the development of miRNA-targeted therapeutic strategies for patients withT2DM and associated complications.